Flavihumibacter fluminis sp. nov., a novel thermotolerant bacterium isolated from river silt. Issue 1 (18th January 2023) - Guo, Bai; Mu, Weidong; Mao, Sidi; Li, Shucheng; Yang, Shaomei; Liu, Aijv; Wei, Shuzhen; Li, Xiuyun; Sang, Feng; Deng, Hongkuan; Dong, Yuling; Liu, Hongliang; et al.
Abstract : A yellow, Gram-stain-positive, strictly aerobic, thermotolerant, non-motile and rod-shaped bacterial strain, designated RY-1 T, was isolated from a silt sample of Fuyang River, Wuqiang County, Hengshui City, Hebei Province, PR China. Cells showed oxidase- and catalase-positive activities. Growth occurred at 20–45 °C (optimum, 37 °C) and pH 6.0–8.0 (optimum, pH 7.0), and in the presence of 0–1.5 % (w/v) NaCl (optimum, 0%). A phylogenetic tree based on 16S rRNA gene sequences revealed that strain RY-1 T formed a phylogenetic lineage with Flavihumibacter members within the family Chitinophagaceae . A comparison of 16S rRNA gene sequences showed that strain RY-1 T was most closely related to Flavihumibacter cheonanensis WS16 T (98.6 %), Flavihumibacter sediminis CJ663 T (97.7 %) and Flavihumibacter solisilvae 3-3 T (97.6 %). The genome size of strain RY-1 T was 4.71 Mb, and the DNA G+C content was 44.3  %. The average nucleotide identity, digital DNA–DNA hybridization and average amino acid identity values between strain RY-1 T and reference strains were all lower than the threshold values for species delineation. Strain RY-1 T contained menaquinone-7 and iso-C15 : 0, iso-C17 : 0 3-OH and iso-C15 : 1 G as the sole respiratory isoprenoid quinone and major cellular fatty acids (≥5 %), respectively. The major polar lipids consisted of phosphatidylethanolamine, three unidentified aminolipids and four unidentified lipids. According to the results of phenotypic, phylogenetic and chemotaxonomic characteristics, strain RY-1 T represents a novel species of the genus Flavihumibacter, for which the name Flavihumibacter fluminis s p. nov. is proposed. The type strain is RY-1 T (=GDMCC 1.2775 T =JCM 34870 T ).